GC-1 mRHBDD1 knockdown spermatogonia cells lose their spermatogenic capacity in mouse seminiferous tubules - Koide SS; Zong Shudong; Miao Shiying; Guan Xin; Li Shuchun; Song Wei; Wang Yong; Wang Linfang (BMC Cell Biology, 2009)
Abstract Background Apoptosis is important for regulating spermatogenesis. The protein mRHBDD1 (mouse homolog of human RHBDD1)/rRHBDD1 (rat homolog of human RHBDD1) is highly expressed in the testis and is involved in apoptosis of spermatogonia. GC-1, a spermatogonia cell line, has the capacity to differentiate into spermatids within the seminiferous tubules. We constructed mRHBDD1 knockdown GC-1 cells and evaluated their capacity to differentiate into spermatids in mouse seminiferous tubules. Results Stable mRHBDD1 knockdown GC-1 cells were sensitive to apoptotic stimuli, PS341 and UV irradiation. In vitro, they survived and proliferated normally. However, they lost the ability to survive and differentiate in mouse seminiferous tubules. Conclusion Our findings suggest that mRHBDD1 may be associated with mammalian spermatogenesis.